Monstruos de papel - Joaquín Díaz (Boletín de Literatura Oral, 2016)
ABSTRACT. The expression «literatura de cordel» uniquely brings together all that kinds of papers that were sold in the street exposed to the attention of the public hanging from a string. The contemplation of that kind of papers used to be in the square or in a market and the editor used to search an effect showing an artistic engraving on the cover. To achieve this engraving attracted without hesitation to who is closer to the seller's specifications, it demanded the collaboration of an artist who return to images which otherwise expressed the words of the author of the text and it required that artist who figures –animals or human– they were identifiable, a desirable general vision and at the same time seem relatively close. Treatment given by some of these artists to the themes of the «pliegos» came to be peculiar to its form created a «style» and a repertoire with own personality and aesthetics. This article discusses some of the recurring themes that influenced the creation of a common long-haul mentality. Resumen: La expresión “literatura de cordel” agrupa unívocamente a todo aquel tipo de papeles que eran vendidos en la calle expuestos a la atención del público colgando de una cuerda. La contemplación del pliego solía hacerse en la plaza o en un mercado y el editor solía buscar un efecto mostrando un grabado en la portada. Para conseguir que ese grabado atrajera sin dudar a quien se acercase al vendedor de pliegos, demandaba la colaboración de un artista plástico que trasladase a imágenes lo que de otro modo expresaban las palabras del autor del pliego y exigía a ese artista que las figuras –de animales o humanas- fuesen identificables, respetasen un deseable plano general y al mismo tiempo parecieran relativamente cercanas. El tratamiento dado por algunos de esos artistas a los temas de los pliegos llegó a hacerse tan peculiar que su forma creó un “estilo” y un repertorio con personalidad y estética propias. En este artículo se analizan algunos de los temas recurrentes que influyeron en la creación de una mentalidad común de largo recorrido.